Gestalt, Navon and Kanizsa illusion processing in CVI, ADHD, and dyslexia Children with Normal verbal IQ - Hokken, Marinke J.; Van Der Zee, Ymie J.; Pereira, Rob Rodrigues; Rours, Ingrid G. I. J. G.; Frens, Maarten A.; van der Steen, Johannes; Pel, Johan J. M.; Kooiker, Marlou J. G. (Frontiers in Human Neuroscience, 2024)
IntroductionGlobal Visual Selective Attention (VSA) is the ability to integrate multiple visual elements of a scene to achieve visual overview. This is essential for navigating crowded environments and recognizing objects or faces. Clinical pediatric research on global VSA deficits primarily focuses on autism spectrum disorder (ASD). However, in children with cerebral visual impairment (CVI) and other neurodevelopmental disorders (ADHD, dyslexia) similar deficits are reported. The aim of this study was to investigate global VSA performance in children with CVI, ADHD, dyslexia and neurotypical children by combing gaze-based measures with conventional neuropsychological tasks.MethodsWe included children aged 6–12 years with CVI (n = 20), ADHD (n = 30), dyslexia (n = 34) and neurotypical development (n = 37), all with normal verbal IQ. Eye tracking measurements were stepwise introduced within three global VSA tasks: Gestalt Closure (no eye tracking), Navon stimuli (eye tracking-based qualitative analysis) and Kanizsa Illusory Contours (KIC; eye tracking-based quantitative analysis). Verbal responses were compared with non-verbal gaze behavior.ResultsChildren with CVI had significantly lower success rates on Gestalt Closure recognition, prolonged verbal response times on Navon stimuli, and decreased verbal and gaze performance on the KIC task compared to all other groups, irrespective of visual acuity. Children with ADHD and dyslexia performed similar to neurotypical children on all tasks.DiscussionThe results suggest а distinct global VSA deficit in children with CVI, which aligns with clinical observations of symptoms in daily life. Incorporating gaze-based analyses provided new information about search strategies beyond verbal answers and made the KIC task more inclusive for children with language and motor disabilities. Assessing global VSA within clinical CVI assessments could improve the differential diagnostic evaluations among children with CVI, ADHD and dyslexia, leading to more personalized treatment approaches.